Nanomedicine as a Potential Tool against Monkeypox - Nura Adam Mohamed; Luisa Zupin; Sarah Ismail Mazi; Hebah A. Al-Khatib; Sergio Crovella (Vaccines, 2023)
Human monkeypox is a rare viral zoonosis that was first identified in 1970; since then, this infectious disease has been marked as endemic in central and western Africa. The disease has always been considered rare and self-limiting; however, recent worldwide reports of several cases suggest otherwise. Especially with monkeypox being recognized as the most important orthopoxvirus infection in humans in the smallpox post-eradication era, its spread across the globe marks a new epidemic. Currently, there is no proven treatment for human monkeypox, and questions about the necessity of developing a vaccine persist. Notably, if we are to take lessons from the COVID-19 pandemic, developing a nanomedicine-based preventative strategy might be prudent, particularly with the rapid growth of the use of nanotechnology and nanomaterials in medical research. Unfortunately, the collected data in this area is limited, dispersed, and often incomplete. Therefore, this review aims to trace all reported nanomedicine approaches made in the monkeypox area and to suggest possible directions that could be further investigated to develop a counteractive strategy against emerging and existing viruses that could diminish this epidemic and prevent it from becoming a potential pandemic, especially with the world still recovering from the COVID-19 pandemic.